The cytoplasmic LSm1-7 and nuclear LSm2-8 complexes exert opposite effects on Hepatitis B virus biosynthesis and interferon responses - Rahman, Naimur; Sun, Jiazeng; Li, Zhili; Pattnaik, Aryamav; Mohallem, Rodrigo; Wang, Mengbo; Kazemian, Majid; Aryal, Uma K.; Andrisani, Ourania (Frontiers in Immunology, 2022)
Despite many studies on host or viral gene expression, how the cellular proteome responds to internal or external cues during the infection process remains unclear. In this study, we used a Hepatitis B Virus (HBV) replication model and performed proteomic analyses to understand how HBV evades innate immunity as a function of cell cycle progression. Specifically, we performed proteomic analyses of HBV-replicating cells in G1/S and G2/M phases, as a function of IFN-α treatment. We identified that the conserved LSm (Like-Sm1-8) proteins were differentially regulated in HBV replicating cells treated with IFN-α. Specifically, in G2/M phase, IFN-α increased protein level of LSm1, the unique subunit of cytoplasmic LSm1-7 complex involved in mRNA decay. By contrast, IFN-α decreased LSm8, the unique subunit of nuclear LSm2-8 complex, a chaperone of U6 spliceosomal RNA, suggesting the cytoplasmic LSm1-7 complex is antiviral, whereas the nuclear LSm2-8 complex is pro-viral. In HBV replication and infection models, siRNA-mediated knockdown of LSm1 increased all viral RNAs. Conversely, LSm8 knockdown reduced viral RNA levels, dependent on N6-adenosine methylation (m6A) of the epsilon stem-loop at the 5′ end of pre-Core/pregenomic (preC/pg) RNA. Methylated RNA immunoprecipitation (MeRIP) assays demonstrated reduced viral RNA methylation by LSm8 knockdown, dependent on the 5’ m6A modification, suggesting the LSm2-8 complex has a role in mediating this modification. Interestingly, splicing inhibitor Cp028 acting upstream of the LSm2-8 complex suppressed viral RNA levels without reducing the 5’ m6A modification. This observation suggests Cp028 has novel antiviral effects, likely potentiating IFN-α-mediated suppression of HBV biosynthesis.